2019
DOI: 10.31557/apjcp.2019.20.12.3789
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as a Surrogate Marker for Autophagy in Peripheral Blood, Correlative Data from Phase I Study of Chloroquine in Combination with Carboplatin/Gemcitabine in Advanced Solid Tumors

Abstract: Background: Autophagy is a catabolic process, utilized constitutionally by body cells to recycle nutrients and to remove unwanted/damaged intracellular constituents. It is enhanced during periods of stress, such as starvation and hypoxia, aiding in cell survival and it is linked to major cellular processes, such as apoptosis and antigen expression. The process has been extensively studied in vitro models or tumor tissue samples with rare application on human subjects. Methods: Plasma samples from 24 advanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Studies have confirmed that several genes are involved and regulate the pathogenesis of asthma, including some autophagy‐related genes, such as autophagy‐related 5 (ATG5) and sequestosome 1 (SQSTM1; Kasembeli et al., 2018 ). In the present study, immunofluorescence and immunohistochemistry results revealed that autophagy marker proteins LC 3B (Abdel Karim et al., 2019 ), Beclin1 (Chen et al., 2020 ), and P62 (Li et al., 2015 ) were unaltered in lung tissues of RSV‐infected mice; however, expression levels of LC 3B and Beclin1, both at the gene and protein levels, were significantly increased following Vit D treatment. The P62 gene and protein levels were significantly decreased, suggesting that the mechanism of Vit D in treating RSV‐induced asthma may involve enhanced autophagy in lung tissue.…”
Section: Discussionsupporting
confidence: 47%
“…Studies have confirmed that several genes are involved and regulate the pathogenesis of asthma, including some autophagy‐related genes, such as autophagy‐related 5 (ATG5) and sequestosome 1 (SQSTM1; Kasembeli et al., 2018 ). In the present study, immunofluorescence and immunohistochemistry results revealed that autophagy marker proteins LC 3B (Abdel Karim et al., 2019 ), Beclin1 (Chen et al., 2020 ), and P62 (Li et al., 2015 ) were unaltered in lung tissues of RSV‐infected mice; however, expression levels of LC 3B and Beclin1, both at the gene and protein levels, were significantly increased following Vit D treatment. The P62 gene and protein levels were significantly decreased, suggesting that the mechanism of Vit D in treating RSV‐induced asthma may involve enhanced autophagy in lung tissue.…”
Section: Discussionsupporting
confidence: 47%
“…LC3B-II appeared to not increase further after 4 h of culture in EBSS with CQ in comparison to 2 h of culture in EBSS with CQ and in KD fibroblasts, particularly, it seemed to decrease. This effect could be possibly explained by hypothesizing that LC3B-II could also be partially lost through other routes such as the exosome release related to autophagy induction, as previously demonstrated [ 26 , 27 ]. However, given these problematics arose considering only LC3B-II formation and to better clarify LC3B-II behaviour, we calculated the ratio between normalized LC3B-II content in cells treated in EBSS with CQ and LC3B-II content in cells in EBSS without CQ, in order to monitor the autophagic flux.…”
Section: Resultsmentioning
confidence: 87%
“…), a combination of CQ or HCQ with CPT increased progressive-free disease and overall survival (OS), although some side effects were reported [96]. Importantly, in the exosomes obtained from the blood plasma of patients who received such treatment, both LC3-B isoforms were detected at advanced time points of the second and third cycles [97].…”
Section: Chloroquine-and Platinum-based Anticancer Drugsmentioning
confidence: 99%